Mrs. Lincoln's sisters : a novel - Chiaverini, Jennifer (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2020)
1875. Elizabeth Todd Edwards reels from news that her younger sister Mary, former First Lady and widow of President Abraham Lincoln, has attempted suicide. The shocking act followed legal proceedings arranged by Mary's eldest and only surviving son that declared her legally insane. The Todd sisters - maternal Elizabeth, peacemaker Frances, envious Ann, and much adored Emilie - had always turned to one another in times of joy and heartache. But when Civil War erupted, the conflict shattered their family. Can they come together as sisters to help Mary in her most desperate hour?-- adapted from jacket
Includes bibliographical references (pages 337-338).
Keywords: Lincoln, Mary Todd, -- 1818-1882 -- Fiction; Edwards, Elizabeth Todd, -- 1813-1888 -- Fiction; Todd family -- Fiction; Edwards, Elizabeth Todd, -- 1813-1888.; Lincoln, Mary Todd, -- 1818-1882.; Todd family; Families -- Fiction; Presidents' spouses -- United States -- Fiction; Sisters -- Fiction; FICTION -- Family Life -- Siblings; FICTION -- Historical; FICTION -- Women; Families; Presidents' spouses; Sisters; Presidents' spouses -- United States -- Fiction; Sisters -- Fiction; United States; Biographical fiction; Historical fiction; Biographical fiction; Fiction; Historical fiction; Historical fiction; Historical fiction; Biographical fiction